Dolphins - Riggs, Kate. (Mankato, Minn. : Creative Education, 2013)
A beginning reader introduction to dolphins, covering their growth process, behaviors, the oceans they call home, and such defining physical features as their fins.
Includes bibliographical references (p. 23) and index.
2.0
K-3
310L
Center for the Collaborative Classroom Curriculum.
Keywords: Dolphins -- Juvenile literature; Dolphins; Readers (Elementary) -- Nonfiction